Extracorporeal Shock Wave Therapy for Lateral Epicondylitis, Lonely or in Combination with Topical Corticosteroid; Which Approach is Superior? - Abasi, Fatemeh; Vahdatpour, Babak; Taheri, Parisa (Galen Medical Journal, 2020)
Background: Lateral epicondylitis (LE) is a common musculoskeletal disorder. Although varieties of modalities have been proposed for its treatment, the outcomes are uncertain, and the responses would diminish early by the time passage. The current study was aimed to assess the efficacy of extracorporeal shock wave therapy (ESWT) merely and in combination with topical corticosteroid for the treatment of LE. Materials and Methods: In the current double-blinded randomized clinical trial, 70 patients with the diagnosis of LE were randomly allocated to two intervention groups of ESWT merely (control group) (n=35) or ESWT plus topical corticosteroid (intervention group) (n=35). The ESWT was performed weekly for three weeks. Topical clobetasol was utilized within 30 minutes before ESWT for the intervention group, while Vaseline gel was used in a similar pattern for controls. Pain based on a visual analog scale (VAS), handgrip strength (HGS) and the Patient-Rated Tennis Elbow Evaluation (PRTEE) were assessed for the patients before the intervention, following the intervention cessation, and within two months post-intervention. Results: Statistically significant improvement was found following both interventions in terms of pain, HGS, and function (P-value0.05). Conclusion: The findings of our study are in favor of ESWT use either merely or in combination with topical steroids for the treatment of LE, while the comparison of the two techniques revealed insignificant differences. [GMJ.2020;9:e1791]